Pemanfaatan Kartografi Digital dalam Pembelajaran IPS di Sekolah Dasar - Dea Ananda Febriani; Melva Zainil (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is specifically designed to explore how the use of digital cartography is applied in Social Sciences learning at the Elementary School level. Digital cartography is a technology that visualizes spatial data, making it easier for teachers and students to understand the concept of location, area, and relationships between spaces more realistically. This study uses a qualitative descriptive approach with subjects of one fifth grade teacher and 25 students in an elementary school. Data were collected through observation, interviews, and documentation. The findings of the study indicate that the use of digital map media such as Google Earth, online thematic maps, and MAPENA (Children's Map Media) can improve students' understanding of spatial material, while motivating them to play an active role in learning. Teachers also consider digital cartography to be very helpful in delivering social studies material, especially related to geography. This study suggests the integration of digital map technology into lesson plans and project-based thematic learning.